PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA-BIOLOGI BERBASIS DISKOVERI-INKUIRI DENGAN SUMBER BELAJAR POTENSI LINGKUNGAN LOKAL KABUPATEN PASURUAN - Ibrohim, Ibrohim; Afiat M, Dyah; Nurdiana, Fatatus R.; Estiningsih, Yuli; Martiana, Cinthiana; N, Fikhi M. (Universitas Sebelas Maret, 2014)
Curriculum 2013 instructed that in learning to use the scientific approach, with one of the suggested method of learning is discovery - inquiry. For more contectual learning science (biology), the use of materials /learning resources from the surrounding environment are needed. Related to this has been done the research and development of learning science (biology) in the Junior Scondary Education with the aim to develop the learning science (biology) discovery – inquiry-based using teaching materials derived from the potential of the local environment in the district of Pasuruan, East Java. Research and development using 4D models (difine, design, develop, disseminate) of Thiagajan et al (1974) were modified. The study involved 6 Department of Biology students who are taking the thesis and 6 teachers in junior partners test target. Each component of the learning device has been validated by one teacher in junior secondary school partner and one lecturer UM Department of Biological. The results showed that the level of validity of each of the component devices are developed, the validity of the syllabus reached 97.5 %, the validity of the Lesson Plan (RPP) reached 96.0 %, the validity worksheets reached 98 %, handouts validity reached 98.5 %, and validity of assessment instruments reached 96 %. From the try out results obtained at the level of adherence to classroom learning scenarios and devices reached 87.5 %. The results also showed that student learning process achievement were improve, whether cognitive, affective, and psychomotor. Based on these results it is suggested that learning science (biology) carried kept in appropriate learning methods and sources of contextual learning environment surrounding potential students. Keywords : development of a learning device, Science (Biology), discovery - inquiry, local potential environment